2023
DOI: 10.3390/jcm12165272
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Transit Times in Health as Determined Using Ingestible Capsule Systems: A Systematic Review

Abstract: Background: Ingestible capsule (IC) systems can assess gastrointestinal (GI) transit times as a surrogate for gut motility for extended periods of time within a minimally invasive, radiation-free and ambulatory setting. Methods: A literature review of IC systems and a systematic review of studies utilizing IC systems to measure GI transit times in healthy volunteers was performed. Screening for eligible studies, data extraction and bias assessments was performed by two reviewers. A narrative synthesis of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
(393 reference statements)
0
4
0
Order By: Relevance
“…The reproducibility of scintigraphy for measuring colonic transit is good and allows evaluation of the stomach, small intestine, and large intestine, even in the pediatric population. It is useful for monitoring cases with intractable constipation using a technique with two radiopharmaceuticals with different half-lives; unfortunately, In 111 is not available in our setting (7).…”
Section: Discussionmentioning
confidence: 99%
“…The reproducibility of scintigraphy for measuring colonic transit is good and allows evaluation of the stomach, small intestine, and large intestine, even in the pediatric population. It is useful for monitoring cases with intractable constipation using a technique with two radiopharmaceuticals with different half-lives; unfortunately, In 111 is not available in our setting (7).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that the proximal part of the gut is responsible for most early GLP-1 responses to meal ingestion [ 135 ]. Multiple studies showing a gastric emptying time of <1 h [ 138 ] underline the possibility that nutrients, especially after a fast transit of liquid meals or glucose solutions, can reach the duodenum in a short time, leading to GLP-1 release from L cells. This could explain the observed peaks in GLP-1 concentrations, even in short-term postprandial protocols with a duration of ∼3 h. As summarized in the same review, the shortest small intestine transit time reported was 3.3 h, leaving a short time for the luminal content to come in contact with L cells located in the jejunum or even the ileum and stimulate the chemo-sensing machinery, leading to the modulation of GLP-1 release.…”
Section: Discussionmentioning
confidence: 99%
“…As it is undisputable that liquids empty from the stomach more quickly than solid meals, the physical state of the test meal applied in the reviewed studies had a decisive effect on L cell-mediated GLP-1 secretion [ 138 ]. In addition, the size of the meal seemed to matter; the late GLP-1 response (30–180 min) to a large meal (520 kcal) was shown to be more pronounced than that to a small meal (260 kcal), possibly due to lower exposure of stimulatory nutrients to the L cells following the small meal [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we observed translocation occurring within 2 hours in our disease models, it is possible that it may occur even faster, within 10–15 minutes as has been reported previously. 13 This is ample time for phage translocation in the colon, where colonic transit time ranges from ~ 16–29 h. 73 , 74 …”
Section: Discussionmentioning
confidence: 99%